STRATEGIES AND CHALLENGES OF GROCERY TRADERS IN FACING ONLINE MARKET COMPETITION - Fauzan Najib; Alwi Rifa’i; Amanda Afriza Putri; Tengku Muhammad Rafly Rachman (PERSPEKTIF: Journal of Social and Library Science, 2024)
Pasar Simpang Limun, as one of the largest traditional markets in Medan, is facing significant challenges due to the emergence of online markets. Changes in consumer shopping patterns that now prefer online shopping have led to a decline in the turnover of grocery merchants in this market. Price competition with cheap imported products, a decrease in the number of customers, and limited adoption of digital technology are the main challenges for traditional traders. This research uses a descriptive qualitative approach with the methods of in-depth interviews, observation, and documentation. The research subjects were purposively selected grocery traders in Simpang Limun Market. The data was analyzed to identify the challenges faced by traders as well as the survival strategies they apply amidst online market competition. The main challenges faced by grocery merchants include price competition with online markets, a decrease in the number of customers, and a decrease in turnover. Their coping strategies include highlighting product quality, adopting digitalization such as cashless payments and local delivery services (Gojek/Grab), and focusing on holidays to increase sales. However, some merchants still rely on conventional methods without utilizing technology. Digitalization and diversification of sales channels are key to maintaining the competitiveness of traditional merchants. Government interventions, such as digital literacy training, subsidies, regulation of imported products, and provision of digital infrastructure, are needed to support the sustainability of traditional markets.